Synthesis and physicochemical characterization of chemically modified chitosan by succinic anhydride - Mello,Karine Gargioni Pereira Correa de (2006)
The N-succinil-chitosan is a chemically modified derivative of the biopolymer chitosan. The succinic anhydride attached to the free amino groups presented along the chitosan's polymer chain imparts to the molecule different physicochemical properties not exhibited before the modification. These chemical modifications enhance chitosan's solubility in slightly acid, neutral and alkaline media. These properties are related to the long alkyl chains attached to hydrophilic parts. In this case the hydrophilic part of D-glucosamine promotes stronger interactions with the water molecules, and consequently, enhances the solubility of the chitosan polymer. Non-modified free chitosan is soluble only in acidic medium (pH < 5.5). These modifications made possible new applications of chitosan in biotechnological area since the solubility in neutral or slightly alkaline solutions is very important in a biological field.